Analyzing Corin–BNP–NEP Protein Pathway Revealing Differential Mechanisms in AF-Related Ischemic Stroke and No AF-Related Ischemic Stroke - Shen, Xiaozhu; Dong, Nan; Xu, Yiwen; Han, Lin; Yang, Rui; Liao, Juan; Zhang, Xianxian; Xie, Tao; Wang, Yugang; Chen, Chen; Liu, Mengqian; Jiang, Yi; et al. (Frontiers in Aging Neuroscience, 2022)
Background: The incidence of atrial fibrillation (AF)-related stroke increases with aging. Natriuretic peptides (NPs) family, including Corin-B type natriuretic peptide (BNP)-neprilysin (NEP) protein levels increased with age and are risk markers of cardiovascular and cerebrovascular diseases, such as AF and cardioembolic stroke. Aging is also linked to epigenetics, specifically DNA methylation. However, only a few studies have investigated the effect of DNA methylation on the NP system. Thus, the present study aimed to investigate whether methylation affects Corin-BNP-NEP protein pathway and contributes to the pathogenesis of AF-associated ischemic stroke. Methods: A total of 82 acute ischemic stroke hospitalized patients were enrolled in this study. The differences in clinical information were compared between the AF-stroke (n=37) and no AF-stroke groups (n=45). CpG methylation in the promoter region of the gene was assessed by a next-generation sequencing-based bisulfite sequencing polymerase chain reaction (BSP). Plasma-soluble Corin and NEP were detected using an ELISA kit. Results: (1) Patients in AF-stroke were older, had higher initial NIHSS score, 90-day mRs, higher D2-dimer, INR, and APTT, and low TG, TC, and HbA1c (all p,0.05). (2) The levels of CpG methylation in the promoter region of the Corin protein gene in the AF-stroke group was significantly lower than that in the no AF-stroke group (p<0.05). The CpG sites with maximal methylation differences between the two groups were CORIN:678, CORIN:682, CORIN:694, and CORIN:700. (3) Serum levels of Corin and BNP in the AF-stroke group were significantly higher than that in the no AF-stroke group (p<0.05). No significant difference was detected in the serum levels of NEP between the two groups. Conclusion: The current findings raise the possibility that the Corin-BNP-NEP protein pathway may be involved in the pathogenesis of AF-related ischemic stroke. Stroke without AF may exhibit hypermethylation of the Corin peptide promoter region in the blood component, which is strongly associated with vascular aging associated with atherosclerosis.